2008
DOI: 10.1021/jf8004977
|View full text |Cite
|
Sign up to set email alerts
|

A Mixture of trans, trans Conjugated Linoleic Acid Induces Apoptosis in MCF-7 Human Breast Cancer Cells with Reciprocal Expression of Bax and Bcl-2

Abstract: The growth inhibitory effect of a mixture of trans, trans conjugated linoleic acid isomers (t, t CLA) was investigated in a human breast cancer cell line, MCF-7, with references to c9, t11 CLA, t10, c12 CLA, and linoleic acid. The t, t CLA treatment effectively induced a cytotoxic effect in a time-dependent (0-6 days) and concentration-dependent (0-40 microM) manner, as compared to the reference and control treatments. The apoptotic parameters were measured on cells treated with 40 microM t, t CLA for 4 days. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
2
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 27 publications
6
54
2
2
Order By: Relevance
“…The MTT-based assay was used to estimate viable cell number [14]. The absorbance was measured at 570 nm using an Anthos model 2020 microplate reader (Anthos Labtech Instruments, Wals., Austria).…”
Section: Cytotoxicity Testsmentioning
confidence: 99%
“…The MTT-based assay was used to estimate viable cell number [14]. The absorbance was measured at 570 nm using an Anthos model 2020 microplate reader (Anthos Labtech Instruments, Wals., Austria).…”
Section: Cytotoxicity Testsmentioning
confidence: 99%
“…Some of the observed changes consistent with the induction of apoptosis include: increased wild-type p53 protein levels, chromatin condensation, increased pro-apoptotic bax and bak protein levels, reduced anti-apoptotic bcl-2 protein levels, increased cytochrome c in the cytosol, and increased cleavage of initiator and effector caspases, reduced COX-2 activity and the generation of PGE 2 [25,51,52,[54][55][56][57]. A recent report indicated that t10,c12 CLA induces apoptosis in TM4t mammary tumour cells using certain components of the endoplasmic reticulum (ER) stress response, an alternative pathway to apoptosis in addition to the classical death receptor ("extrinsic") or mitochondrial ("intrinsic") pathways [53].…”
Section: Induction Of Apoptosismentioning
confidence: 98%
“…또한 심근경색은 섬유질이 많은 콩, 현미, 잡곡, 등푸른 생선, 딸기 등의 섭취로 예방할 수 있다 [4,28,30]. 최근 conjugated linoleic acid (CLA)는 1987년에 항암성 물질 로 개발 [11]된 이후, 항당뇨성, 항관절염성 등에 관하여 많은 연구가 수행되었다 [1,8,9,[11][12][13][14][15]21,22]. Lee (Fig.…”
Section: 서 론 심근경색(Myocardial Infarction)은 관상동맥의 폐쇄에 따 른 심근의 허혈로 심근세포의unclassified